The impact of social media on the consumer tendencies of store patrons in the Asir region - Almutairi, Adnan Essa; Al Obaid, Hussein Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to analyze the impact of social media on consumers' buying behavior in Aseer region, and the research community included customers of stores in Aseer region. The data of the study was collected from a sample of (259) individuals, and to achieve the research objectives, the descriptive-analytical method and a questionnaire were used as tools for data collection. The research findings indicated that there is a statistically significant effect of the determinants of social media, where the accessibility determinant explains (4.1%) of customers' buying behavior in Aseer region, the credibility determinant explains (1.4%) of their buying behavior, and the technical effects determinant explains (56.9%) of the total customers' buying behavior in Aseer region. However, the interaction determinant did not show any significant effect on customers' buying behavior. The study recommended that stores in Aseer region should be interested in diversifying their presence on social media and intensifying the use of interactive media, especially through smartphones using communication applications such as WhatsApp. Store owners in Aseer region must also pay more attention to privacy and electronic security legislation, as well as consider the credibility and quality as key features in e-shopping to contribute to customer loyalty. Stores should also consider designing attractive and appropriate pages that suit customers' needs and tastes. Furthermore, store owners should analyze customer feedback in terms of topics, trends, characteristics, and interaction patterns, which will increase their overall satisfaction with the store's performance.
Keywords: Social media; Consumption Propensity